2013
DOI: 10.3389/fnhum.2013.00618
|View full text |Cite
|
Sign up to set email alerts
|

Flexible spatial perspective-taking: conversational partners weigh multiple cues in collaborative tasks

Abstract: Research on spatial perspective-taking often focuses on the cognitive processes of isolated individuals as they adopt or maintain imagined perspectives. Collaborative studies of spatial perspective-taking typically examine speakers' linguistic choices, while overlooking their underlying processes and representations. We review evidence from two collaborative experiments that examine the contribution of social and representational cues to spatial perspective choices in both language and the organization of spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
(131 reference statements)
3
20
0
Order By: Relevance
“…It is our view that the evidence shows that although the inherent structure of an array of objects can influence recall it would be premature to conclude that intrinsic cues are the primary determinant of recall performance. It appears that people consider multiple cues for reference frame selection, a notion consistent with evidence presented by Galati and Avraamides (2013).…”
Section: Discussionsupporting
confidence: 58%
“…It is our view that the evidence shows that although the inherent structure of an array of objects can influence recall it would be premature to conclude that intrinsic cues are the primary determinant of recall performance. It appears that people consider multiple cues for reference frame selection, a notion consistent with evidence presented by Galati and Avraamides (2013).…”
Section: Discussionsupporting
confidence: 58%
“…With respect to the second question, in other work, we have examined specifically whether speakers' perspective choices are in fact successful at minimizing pairs' collective effort, as indicated by performance outcomes (Galati & Avraamides, ). By examining the number of conversational turns that pairs from the present corpus took to complete the task and the degree of distortion in their tabletop reconstructions, we confirmed that speakers' description strategies generally facilitated coordination.…”
Section: Discussionmentioning
confidence: 99%
“…When learning occurred from two views, one aligned and one misaligned with the axes of the surrounding room, participants selected a reference frame parallel to the aligned view, and performance when imagining perspectives parallel to the misaligned view was no better than when imagining non experienced views. Those results, together with the body of research on spatial memory, indicate that reference frame selection is influenced by a conjunction of experience-based and environment-based factors (Galati & Avraamides, 2013;Hintzman, O'Dell, & Arndt, 1981;Kelly & McNamara, 2008;Kelly, Sjolund, & Sturz, 2013;Marchette, Yerramsetti, Burns, & Shelton, 2011;Meilinger, Riecke, & Bülthoff, 2014;Mou & McNamara, 2002;Street & Wang, 2014;Werner & Schmidt, 1999;Yamamoto & Shelton, 2005).…”
mentioning
confidence: 93%